A phase II study of omacetaxine mepesuccinate for patients with higher‐risk myelodysplastic syndrome and chronic myelomonocytic leukemia after failure of hypomethylating agents. Issue 1 (15th November 2018) - Short, Nicholas J.; Jabbour, Elias; Naqvi, Kiran; Patel, Ami; Ning, Jing; Sasaki, Koji; Nogueras‐Gonzalez, Graciela M.; Bose, Prithviraj; Kornblau, Steven M.; Takahashi, Koichi; Andreeff, Michael; Sanchez‐Petitto, Gabriela; et al.
Abstract: The outcome of patients with myelodysplastic syndromes (MDSs) after failure of hypomethylating agents (HMAs) failure is poor with a median overall survival (OS) of only 4‐6 months. Omacetaxine mepesuccinate (OM) is safe and effective in myeloid malignancies but has not been studied in MDS with HMA failure. We conducted a phase II study of OM in patients with MDS or chronic myelomonocytic leukemia (CMML) who had previously failed or been intolerant to HMAs. Patients received OM at a dose of 1.25 mg/m 2 subcutaneously every 12 hours for 3 consecutive days on a 4‐ to 7‐week schedule. The primary endpoints were the overall response rate (ORR) and OS. A total of 42 patients were enrolled with a median age of 76 years. The ORR was 33%. Patients with diploid cytogenetics were more likely to respond to OM than were those with cytogenetic abnormalities (58% vs 23%, respectively; P = .03). Overall, the median OS was 7.5 months and 1‐year OS rate was 25%. Patients with diploid cytogenetics had superior OS to those with cytogenetic abnormalities (median OS 14.8 vs 6.8 months, respectively; P = .01). Two patients had ongoing response to OM of 2 years or longer (both MDS with diploid cytogenetics and RUNX1 mutation). The most common grade ≥ 3 adverse events were infections in 11 patients (26%), febrile neutropenia in 4 (10%), and hemorrhage in 3 (7%). Overall, OM was safe and active in patients with MDS or CMML who experienced HMA failure. These results support the further development of OM in this setting.